Managing Islamic Character Education Trough Institutional Isomorphism (Learning From Junior High School Of Progresif Bumi Shalawat, Sidoarjo Coupled - Institutional System) - Rohanah Hidayati, Titiek (International Journal of Educational Research & Social Sciences, 2022)
Until now, the huge discourse of character education is still on projector explaining of what character education is, where the sources of ethical productions came from, and how it implemented in the educational institution; in diverse and vast varies. Informal education, like what is regulated by the government, the sources of characters are studied and formulated based on character education conferences and experts or scholars' consensuses. In micro-institution, character education is delivered according to teacher experiences and knowledge. But, the distinct point is how character education is implemented inIslamic boarding school; beyond the formal and informal process of the Islamic education process, as formulated in Junior High School Progresif Bumi Shalawat Sidoarjo. This integrative school formulated the concept of character through the Prophet Muhammad's name; Musamih (tolerant), Umana’ (trustworthy), Harish (eager), Adib (noble), Mufakkir (thinker), Muhaqqiq (the inquirer), Ashil (Resolute), Duror (Pearls). So that, this article will explore how these finding terms of character are disseminated and transmitted, institutionally, to all students, and will be frame-analyzed by shifting of isomorphism theory of organization. In the end, this article will argue that character education can only be implemented effectively by isolated space which is attributed with Islamic boarding school based-values.